The Methods of Evaluation of Companies Financial Condition and Solvency for the Audit Purposes - Korenik, Dorota (Metody oceny kondycji finansowej i wypłacalności przedsiębiorstw do celów audytu, 2010)
This article describes the main methods of estimation of financial condition and solvency, used for finding high risk audit areas and necessary audit procedures application to obtain the necessary audit evidence. The author gives the characteristic of the Ukrainian practice indices and ratios required by Ukrainian Securities and Financial Market Commission for citing in an audit report, especially during economic crisis. The author pointed out in the article that an auditor has to modify the audit report adding an emphasis of matter paragraph which may contain information about the material uncertainty of the ability to continue business activity by the company.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 142, s. 11-15
Keywords: ochrona zdrowia; zapobiegliwość indywidualna; rynkowe instrumenty finansowe